2014
DOI: 10.1111/nure.12145
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of polyunsaturated fatty acids for dry eye syndrome: a meta-analysis of randomized controlled trials

Abstract: Dry eye syndrome (DES) is a common ocular disease that significantly affects the quality of life. Polyunsaturated fatty acids (PUFAs) have been used to treat DES; however, randomized controlled trials (RCTs) of PUFA therapy yield discordant results. The objective of this study was to clarify the effects of PUFAs on DES through meta-analysis of all relevant RCTs. To do so, a comprehensive search of PubMed, Embase, the Cochrane Library, ISI Web of Science, and unpublished data was conducted. The changes in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
1
29
0
1
Order By: Relevance
“…Similar clinical improvements, as quantified by a relative decrease in tear osmolarity and an attenuation of dry eye symptoms, has recently been reported in another ω‐3 EFA intervention trial, involving a higher daily dose of ω‐3 EFAs (1680 mg EPA + 560 mg DHA) for 12 weeks . Our findings suggest that providing neurotrophic support to corneal nerves is linked to an alleviation of DED symptoms with ω‐3 EFA supplementation . Indeed, the restoration of corneal nerve topography, using autologous serum tears, has recently been shown to attenuate patient‐reported photoallodynia in severe corneal neuropathy …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar clinical improvements, as quantified by a relative decrease in tear osmolarity and an attenuation of dry eye symptoms, has recently been reported in another ω‐3 EFA intervention trial, involving a higher daily dose of ω‐3 EFAs (1680 mg EPA + 560 mg DHA) for 12 weeks . Our findings suggest that providing neurotrophic support to corneal nerves is linked to an alleviation of DED symptoms with ω‐3 EFA supplementation . Indeed, the restoration of corneal nerve topography, using autologous serum tears, has recently been shown to attenuate patient‐reported photoallodynia in severe corneal neuropathy …”
Section: Discussionsupporting
confidence: 83%
“…Omega-3 EFAs bias systemic prostaglandin metabolism towards the production of anti-inflammatory eicosanoids, which limit and resolve inflammation. 8 As summarised in a recent systematic review and meta-analysis, 9 several small clinical trials have investigated the use of oral x-3 EFA supplements for treating DED. Together, these investigations report promising findings in terms of reducing dry eye symptoms and improving tear stability, however, the mechanisms underlying the potential clinical benefits are not entirely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of a systematic review included nine double-blind randomised controlled trials (involving a total of 716 patients) assessing the effects of polyunsaturated fatty acids (from fish oil, buckthorn, evening primrose oil, flax seed, and borage oil). 31 Supplementation improved the OSDI symptom score, relieved burning and eye watering, and reduced inflammatory response on the ocular surface, but had no effect on tear volume or ocular surface stability. Large scale randomised controlled trials are needed to confirm an effect.…”
Section: Other Treatments For Dry Eyementioning
confidence: 91%
“…23 The review included nine RCTs examining 716 patients with either Sjögren’s Syndrome or xerophthalmia. The review authors concluded that while there was no evidence of benefit from oral omega-3 fatty acids with regard to tear volume, ocular surface stability, and tear film staining, patients receiving this treatment appeared to fare better in terms of ocular symptoms (measured through the ocular surface disease index) when compared with patients receiving control interventions.…”
Section: Resultsmentioning
confidence: 99%